Identification of Molecular Marker Based on MYB Transcription Factor for the Selection of Indonesian Fine Cacao (Theobroma cacao L.) - Lukita Devy; Indah Anita-Sari; Tengku Imam Saputra; Agung Wahyu Susilo; Ade Wachjar; . Sobir (Indonesian Coffee and Cocoa Research Institute, 2018)
Indonesia is the third largest cacao (Theobroma cacao L.) producer in the world and also well-known for its fine cacao varieties (Java fine-flavor cacao). Indonesian fine cacao breeding program will be accelerated by early detection of its specific trait through the use of molecular marker. One of the traits thatcould differentiate fine and bulk cacao, in this case Criollo and Forastero, respectively, is the pod color. Previous research reported that MYB transcription factor gene regulated cacao pod color and was able to differentiate Criollo from Forastero. The gene involved in the control of plant-specific processes including primary and secondary metabolism, cell fate and identity, developmental processes and responses to biotic and abiotic stresses. This research aimed to identify the diversity of Indonesian fine and bulk cacao based on MYB nucleotide sequence fragments. Identification of the MYB nucleotide sequence was conducted by DNA isolation from cacao leaves and specific primer design based on two cacao MYB transcription factor ene accessions. These primers were used to evaluate the diversity of three Indonesian fine cacao (DRC 16, PNT 16, and ICCRI 01) and two bulk cacao (PA 191 and ICCRI 03) clones. The cluster analysis showed that this specific primer is similar to other MYB gene accessions in Malvaceae family (Theobroma, Herrania, Gossypium). It is also able to differentiate bulk and fine cacao in accordance to their pedigree. The primer developed in this study could be used for further analysis of Indonesian fine cacao molecular marker.